Junior High School Students’ Perceptions on the Implementation of Montessori Approach in Vocabulary Learning - Setiawan, Niko Albert; Ena, Ouda Teda (Universitas Nusantara PGRI Kediri, 2019)
Montessori approach is mostly used in the kindergarten and elementary school, especially in Indonesia. To explore the approach in the higher level of education, the research took place in a private Montessori Junior High School in Yogyakarta, Indonesia. This study is intended to investigate the students’ perceptions on the implementation of Montessori approach to improve their vocabulary due to the fact that vocabulary is central to language learning. The research participants are students in grades seven and eight. There were three research instruments in this study, namely observations, questionnaire, and Focus Group Discussion (FGD). Three different research instruments were used to make sure that the data obtained was valid. The researchers crosschecked the results from each instrument to triangulate data consistency. Based on the findings, the students have positive perceptions on the implementation of Montessori approach for vocabulary learning. The implementation of Montessori approach promotes its unique learning activities, teacher’s personal guidance, and students’ learning awareness, internal motivation, and interest. The students perceived that the implementation of Montessori approach can improve their vocabulary.